Fractional differential inclusions with anti-periodic boundary conditions in Banach spaces. - Ahmed Ibrahim (Electronic Journal of Qualitative Theory of Differential Equations, 2014)
The main purpose of this paper is to provide the theory of differential inclusions by new existence results of solutions for boundary value problems of differential inclusions with fractional order and with anti-periodic boundary conditions in Banach spaces. We prove existence theorems of solutions under both convexity and nonconvexity conditions on the multivalued side. Meanwhile, the compactness of the set solutions is also established.